Optimizing the rotation cycle of previous crops increases crop yield and environmental sustainability in paddy field rotation - Siyu Gun; Jing Liu; Fangyuan Huang; Junwei Wang; Hui Cheng; Qigan Li; Zhan Jiang; Yonghua Zhu; Ni Ma (Crop Journal)
Global food production faces enormous challenges in increasing yields while promoting environmental sustainability. A field experiments in the ecotone between the Yangtze River Basin and the Huang-Huai-Hai Plain evaluated the effects of changing preceding crop rotation cycles (wheat and rapeseed) on long-term wheat-rice (W) and rapeseed-rice (R) rotation systems. A comprehensive evaluation of crop rotation systems was conducted using life cycle assessment, considering productivity, economic benefits, carbon footprint (CF), and soil health. Compared with fallow-rice rotation (F), alternating rapeseed and wheat rotations increased equivalent yield by 60.4%–82.2%, reduced CF by 0.3%–5.7%, and improved soil health by 0.3%–47.5%. Additionally, adding rapeseed to rotations increased soil nutrient content and raised soil organic carbon stocks by 31.3%–40.5%. The 3R rotation (3-year rapeseed-rice and 1-year wheat-rice) boosted rice yield by 82.2% and annual economic benefits by 84.4%, offering an effective model for optimizing long-term R rotations. Similarly, the 2W rotation (2-year wheat−rice and 1-year rapeseed rice) enhanced rice yield by 70.0% and annual economic benefits by 65.9%, providing a successful example for optimizing long-term W rotations. The 3R rapeseed-based rotation and the 2W wheat-based rotation demonstrated good environmental sustainability. These rotation systems have broad potential in sustainable intensive farming, especially in China and similar regions.